ANALISIS STAKEHOLDERS DALAM PENGEMBANGAN PROGRAM DIKLAT DI BALAI DIKLAT APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN STAKEHOLDERS ANALYSIS IN DEVELOPMENT OF TRAINING PROGRAM ON TRAINING OFFICE OF APPARATUS MINISTRY OF MARINE AFFAIRS AND FISHERIES - Yudistira Adi Nugroho (Jurnal Manajemen dan Bisnis Kreatif, 2019)
The results of the identification of training needs indicate that there are still several types of training that cannot be implemented. One of the contributing factors is the development of training programs in both technical training and functional training have not been fully implemented. This study aims to analyze the role and interests of stakeholders in the development of training programs at the Training Office for Apparatus of the Ministry of Marine Affairs and Fisheries.